A systematic review of energy and mass fluxes, and biogeochemical processes in seasonally dry tropical forests and cactus ecosystems - Jardim, Alexandre Maniçoba da Rosa Ferraz; Morais, José Edson Florentino de; Souza, Luciana Sandra Bastos de; Lopes, Daniela de Carvalho; Silva, Marcos Vinícius da; Pandorfi, Héliton; Oliveira-Júnior, José Francisco de; Silva, Jhon Lennon Bezerra da; Steidle Neto, Antonio José; Morellato, Leonor Patrícia Cerdeira [UNESP]; de Lima, João L.M.P.; Silva, Thieres George Freire da (Elsevier, 2023)
Hostile climatic conditions, including high water deficit in the soil-atmosphere system characterize regions with arid and semi-arid climates. Local landscapes with climates of low rainfall and relative humidity, and high air temperature, such as regions of sub-humid, semi-arid, and arid zones, cover approximately 45.4% of the entire land surface of the planet, to which the biomes with dry forests occupy a total area of 1079 × 104 km2. Thus, this review aims to quantify the processes and changes in energy, water, and carbon fluxes and their interactions with the surfaces of terrestrial ecosystems of Caatinga and cacti in semi-arid environments. Studies report that forests in arid and semi-arid environments show resilience to local diversity, prominent in the interrelationship of species, which favors the survival of individuals with changes in the ecological niche. One of the main modifications in land use and land occupation in dryland landscapes is the implementation of agriculture. There is evidence that poor land use can negatively affect soil carbon stocks. Furthermore, carbon and energy fluxes in terrestrial ecosystems undergo significant changes with the removal of native vegetation. Therefore, the damage caused by deforestation can cause severe problems in the energy and carbon balance, compromising species' survival. Finally, we emphasize that crassulacean acid metabolism plants can be an alternative in places with serious environmental degradation problems.
Keywords: Caatinga; Cacti; Carbon stocks; Deforestation; Energy balance